2023
DOI: 10.1186/s40001-023-01441-8
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of the fecal microbiota and circulating microRNA-16 in IBS subjects with Blastocystis infection : a case–control study

Alireza Olyaiee,
Abbas Yadegar,
Elnaz Sadat Mirsamadi
et al.

Abstract: Irritable bowel syndrome (IBS) is a prevalent gastrointestinal (GI) tract disorder. Although the main reason for IBS is not clear, the interaction between intestinal microorganisms and the gut barrier seems to play an important role in pathogenesis of IBS. The current study aimed to investigate the effect of Blastocystis on the gut microbiota profile and the circulation levels of microRNA (mir)-16 of IBS patients compared to healthy subjects. Stool and blood samples were collected from 80 participants includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Notably, these miRNAs and others, such as miR-18a*, miR-4802, miR-515-5p, and miR-1226-5p, shape the composition of gut microbiota, ultimately affecting the pathophysiology of intestinal disorders in the host [ 91 ]. Olyaiee et al [ 92 ] tested the serum and feces of patients with IBS and found that miR-16 was downregulated, and the relative abundance of Thickettsia , Actinobacteria , and Enterococcus faecalis increased. Mansour et al [ 93 ] found that the number of coliform bacteria increased in patients with IBS, while miR-199b expression decreased, particularly in patients with IBS-D, and intestinal flora negatively correlated with miR-199b.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, these miRNAs and others, such as miR-18a*, miR-4802, miR-515-5p, and miR-1226-5p, shape the composition of gut microbiota, ultimately affecting the pathophysiology of intestinal disorders in the host [ 91 ]. Olyaiee et al [ 92 ] tested the serum and feces of patients with IBS and found that miR-16 was downregulated, and the relative abundance of Thickettsia , Actinobacteria , and Enterococcus faecalis increased. Mansour et al [ 93 ] found that the number of coliform bacteria increased in patients with IBS, while miR-199b expression decreased, particularly in patients with IBS-D, and intestinal flora negatively correlated with miR-199b.…”
Section: Discussionmentioning
confidence: 99%